Notorious in the neighborhood : sex and families across the color line in Virginia, 1787-1861 - Rothman, Joshua D. (The University of North Carolina Press, 2003)
This text examines interracial sexual relationships under slavery. While laws militated against interracial sex in Virginia before the Civil War it was ubiquitous throughout the state. The customery toleration of sex across the colour line both supported and undermined racism.
Keywords: Miscegenation (Racist theory) -- Virginia -- History.; Miscegenation (Racist theory) -- Social aspects -- Virginia -- History.; Multiracial people -- Virginia -- History.; Interracial marriage -- Law and legislation -- Virginia -- History.; Virginia -- Race relations -- History.; Métissage -- Virginie -- Histoire.; Métissage -- Aspect social -- Virginie -- Histoire.; Virginie -- Relations raciales -- Histoire.; SOCIAL SCIENCE -- Sociology -- Marriage & Family.; Interracial marriage -- Law and legislation; Miscegenation (Racist theory); Miscegenation (Racist theory) -- Social aspects; Race relations; Multiracial people; Virginia; Ethnische Beziehungen; Interethnische Ehe; Gesetzgebung; Rassenverhoudingen.; Seksuele betrekkingen.; Familierelaties.; Electronic books.; History